Effects of translocation on survival of nuisance bears. (24th March 2021) - Bauder, J. M.; Ruid, D.; Roberts, N. M.; Kohn, B.; Allen, M. L.
Abstract: Effective mitigation of human–wildlife conflict should aim to reduce conflicts while also minimizing wildlife mortality. Translocation is often used to mitigate human–wildlife conflict but translocated individuals may have reduced survival, which could negatively affect population growth and social acceptance of translocation as a management tool. Yet, non‐translocated nuisance individuals may also have low survival due to inherent risks associated with nuisance behavior. We used a 38‐year dataset of 1233 marked and translocated nuisance American black bears ( Ursus americanus ) as a model system with which to evaluate the impacts of translocation on nuisance bear survival. We used multi‐state mark‐recapture models to estimate annual harvest and non‐harvest mortality rates and tested for effects of translocation distance and harvest rate on recapture and both mortality rates. Recapture probability increased with translocation distance but 75% of translocated bears were translocated ≤75 km and recapture probabilities were <0.05 across these distances. Survival was 0.43 for adult males, 0.56 for adult females, and 0.38–0.40 for yearlings. However, increasing translocation distance reduced both harvest and non‐harvest mortality (β = −0.0044, 95% CI = −0.0081 to −0.0006 and β = −0.0020, 95% CI = −0.0051 to 0.0011, respectively) showing that increasing translocation distance does not negatively impact survival. Our survival estimates were generally lower than those reported for non‐nuisance American black bear populations (0.67–0.83), which likely reflects risks associated with nuisance behavior, such as proximity to human dwellings, agriculture, or roads which in turn may increase harvest and/or road mortality. Our results show that translocation is a useful approach for mitigating human–bear conflict that does not always negatively affect survival. Lower survival of nuisance bears suggests that biologists should focus efforts on reducing the incidences of human–wildlife conflicts (e.g., removing anthropogenic food sources). Abstract : Managing human–carnivore conflicts is an important challenge in carnivore conservation. Translocation is often used to manage human–carnivore conflicts, yet may result in reduced carnivore survival. We used 38 years of mark‐recapture records of translocated nuisance American black bear ( Ursus americanus ) to understand how translocation affects survival. We found that increasing translocation distance did not increase harvest or non‐harvest mortality, but that survival was lower relative to non‐translocated non‐nuisance populations. Our results show that translocation is a useful approach for mitigating human–bear conflict that does not always negatively affect survival and that biologists should focus efforts on reducing the incidences of human–wildlife conflicts.